ENTREPRENEURIAL FINANCE: ANGEL INVESTING AS A SOURCE OF FUNDING HIGH-GROWTH START-UP FIRMS - SONJA MARKOVA; TATJANA PETKOVSKA-MIRČEVSKA (Annals of the University of Petrosani: Economics)
One of the most difficult components in starting and growing a new venture is securing funding and other resources to sustain the firm’s survival and growth. Funding for many new ventures comes from a large, yet relatively unidentified, group called angel investors. This paper provides an overview of angel investing as a source of funding for start-up firms.